Scanning Probe Microscopy Physical Property Characterization at Nanoscale - Nalladega, Vijay (IntechOpen, 2012)
Scanning probe microscopy (SPM) is one of the key enabling tools for the advancement for nanotechnology with applications in many interdisciplinary research areas. This book presents selected original research works on the application of scanning probe microscopy techniques for the characterization of physical properties of different materials at the nanoscale. The topics in the book range from surface morphology analysis of thin film structures, oxide thin layers and superconducting structures, novel scanning probe microscopy techniques for characterization of mechanical and electrical properties, evaluation of mechanical and tribological properties of hybrid coatings and thin films. The variety of topics chosen for the book underlines the strong interdisciplinary nature of the research work in the field of scanning probe microscopy.